PENGEMBANGAN BAHAN AJAR MANAJEMEN KEARSIPAN BERBASIS METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Bukhori, Imam; Joyoatmojo, Soetarno; Susilaningsih, Susilaningsih (Jurnal Pendidikan Insan Mandiri, 2016)
The objectives of this research are as follows: (1) to produce the demonstration method-based Archival Management learning material; and (2) to investigate the effectiveness of the demonstration method-based Archival Management learning material to improve the students? learning achievement.This study used the demonstration-based research and development (R&D) method. The measure (syntax) used in this research was the one claimed by Sugiyono. The subjects for the field experimentation were the students as many as 38 of the Study Program of Office Administration, the Faculty of Economics, State University of Malang, Offering( Class) R of 2011, who were taking the course of Archival Management. The data of research were validated by three experts, namely: textbook expert, language expert, and learning material expert.The development of learning material for the demonstration method-based Archival Management uses the R&D model claimed by Sugiyono. Its characteristics are as follows: it uses chart images, pictures or photos which resemble archival articles/materials/devices/equipment so that the students are easy to study the learning materials on the main topic of discussion of Incoming and Outgoing Mail Handling, and Archival Systems of Mail Numbers and Dates. The result of questionnaire validations by the textbook, language, and learning material experts shows that the average percentage is 95%, meaning that in general the learning material of Archival Management is valid or can be used effectively. The students? pre-test score is 68.05. Following the application of the developed learning material, the average score becomes 80.63. This proves that the use of the demonstration method-based Archival Management learning material can effectively improve the students? learning result. In addition, the result of hypothesis testing i.e. zero hypothesis (Ho) which reads ?The use of the demonstration method-based Archival Management learning material in the teaching and learning process is worse than or similar to the other learning methods in improving the students? learning result.? is rejected. This means that the demonstration method-based Archival Management learning material can effectively improve the students? learning result. Keywords:     Development of learning material, demonstration method, learning result